Association between Marital Status and the Outcome of Teenage Pregnancy: A Retrospective Review in Year 2009-2012 in Hospital Ampang - Khalid, S; Aris, MSM (Univ Putra Malaysia Press, 2024)
Indexed by WOS/ Scopus